Learning and teaching information skills: two systems interconnected from activity theory and information behavior models - Uribe Tirado, Alejandro (Pensando Psicología, 2013)
This paper presents the theoretical and conceptual results of the research project “Design, implementation and evaluation of a formation proposal on information alphabetization through a virtual learning environment at a university level”, of the eafit University- Universidad de Antioquia, 2008-2010, carried out by the research group “Información, Conocimiento y Sociedad” (Information, Knowledge and society). Grounded on the fundamentals of Activity Theory and after reviewing 29 information behavior models and 6 models of interaction for on-line education, this research was used to propose: 1) a general and integrating model for information behavior; 2) the graphic representation of learning and teaching in information skills (ci) or information alphabetization (alfin) as interconnected activity systems that generate different processes for an adequate teaching design for ci-alfin programs in a university context. This model and graphical representation have been used in practice for the design of a curricular course for students from the Universidad de Antioquia.